Mainstreaming Islamic Ecotheology through Participatory Action Research: Restoring Santri’s Environmental Awareness in an Indonesian Pesantren - M. Athoiful Fanan; Fathul Fauzi (Tafkir: Interdisciplinary Journal of Islamic Education, 2024)
Environmental degradation and the increasing frequency of ecological disasters highlight the urgency of integrating religious values into environmental awareness initiatives. Islamic ecotheology offers a theological framework that emphasizes human responsibility as khalīfat Allāh fī al-arḍ (stewards of the earth). This study aims to examine the process and outcomes of mainstreaming Islamic ecotheology in restoring santri’s environmental awareness at Pondok Pesantren Sumber Pendidikan Mental Agama Allah (SPMAA), Lamongan, Indonesia. Employing a qualitative approach with a Participatory Action Research (PAR) design, this study involved pesantren stakeholders, santri, and the surrounding community through focus group discussions, educational sessions, media campaigns, and collective environmental actions. The findings indicate that the participatory internalization of Islamic ecotheological values successfully enhanced santri’s ecological awareness, both conceptually and practically. This process resulted in the formulation of green fiqh concepts, the implementation of green da’wah through digital media, and concrete environmental actions within the pesantren. The study contributes to Islamic educational discourse by demonstrating that participatory-based ecotheological approaches can effectively position pesantren as agents of environmental transformation and disaster awareness within grassroots communities.